(untitled) (Global Journal of Science Frontier Research, 2016)
The present field investigation was undertaken to access the efficacy of different treatment schedules during rabi season from November to February in 2013-14 and 2014-15 respectively against whitefly, Bemisia tabaci Genn. (Aleyrodidae: Hemiptera) on potato at District Seed Farm, Department of Agriculture, Government of West Bengal, P.O. -Burdwan, Dist. -Burdwan and West Bengal. All the treatment schedules were significantly superior over control in decreasing the whitefly population on potato but not all around the growing season of the crop. Among the different schedules, T 1 in which phorate 10 G @ 1.5 kg a.i./ha was applied to the soil at the time of planting and then spraying of chlorpyriphos 20 EC @ 0.5 kg a.i./ha, imidacloprid 17.8 SL @ 0.04 kg a.i./ha and cartap hydrochloride @ 0.75 kg a.i./ha were done at 40, 55 and 70 days after planting (DAP), respectively was most effective in reducing the pest population over untreated check plot, which was followed by T 2 , T 3 , T 5 , T 6 , T 4 , respectively.